PENGARUH MODEL PEMBELAJARAN PICTURE AND PICTURE BERBASIS KARAKTER TERHADAP KOMPETENSI PENGETAHUAN IPS - Leoniari, Ni Luh De (Journal for Lesson and Learning Studies, 2018)
The study aimed to determine the significant difference of knowledge competence in Social Science to group of students taught by Picture and Picture learning model based the Character and group of students taught by conventional learning in grade IV SD Gugus III Kuta Utara, academic year of 2017/2018. This study was a quasi-experimental research with nonequivalent control group design. The population of this study was the whole grade IV SD Gugus III Kuta Utara which consist of 15 classes and 506 students from 7 schools. The sample was obtained by random sampling. The sample in this study were the students of grade IVA SD No. 1 Kerobokan Kaja as experiment group and fourth grade students of SD No. 2 Kerobokan Kaja as control group. The data collected were knowledge competence in Social Sience data and analyzed using t test. The result of data analysis obtained by tc = 4,103 at 5% significance level and dk = 62 obtained tt value = 2,000 so tc = 4,103 > tt = 2,000, H0 rejected. This means that there is a significant difference of knowledge competence in Social Science of students who are taught using Picture and Picture learning model based on the Character and students who are taught using conventional learning. The mean value gain normalize score in the group that was taught using Picture and Picture learning model based the Character wasÂ  1=0,50 > 2= 0,34 The mean value gain normalize score in the group that was taught using conventional learning , so the conclusion of this study is the Picture and Picture learning model based the Character effect to knowledge competence in Social Sience of fourth grade students SD Gugus III Kuta Utara in academic year 2017/2018.